Petrogenesis, Tectonic Setting and Mineral Potentials of Dlam and Uding areas of Hong, Northeastern Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
The study area is located in Northeastern Nigeria. It lies between longitudes 12° 52’30” and12°59’30” E, and latitudes 10° 07’00” and N 10° 16’00”. It is about 116 km2 in areal extent andlies in the south central of Hawal Massif. It is bounded to the west and south by the Gongolaand Yola arms of the Benue Trough. Northwards, it is bounded by the Chad Quaternary Basin.The major rock units in the study area include fine to coarse grained granites, fine grainedgranites syenite, and quartz syenite. The rocks are characterized by a wide range in SiO2 (58.7-73.0 wt.%,), alkaline to Calc-alkaline affinity, syn- to late orogenic signatures, metaluminoustoperalkaline composition. The granitoids in the study area are categorized into alkaline and calc-alkaline suite based on their geochemical characteristics. The high K2O and Na2O (4.86-6.99wt.% and 4.62-6.98 wt.%. respectively) and low Y/Nb ratio of < 2 for the alkaline suites aretypical of granitoid suites that are commonly considered as derivatives of mantle sources. Allthese data indicate that the rocks in the study area are probably formed from fractionalcrystallization of magmas derived from the lithospheric mantle, which emplaced the syenites,quartz syenite and alkaline granites. The calc-alkaline granite is characterized by higher SiO2compositionand Y/N ratio >2 exhibiting crustal affinity that was probably formed by the meltingof the lower crust. This study indicates that the area under study was affected by two majortectonic (magmatic), which suggest that the calc alkalic granitoids were emplaced earlierduring syn-collision by partial melting of Paleoproterozoic crust. Magmatism during the secondtectonic episode resulted in to the emplacement of the alkaline granitoids via fractionalcrystallization and crustal assimilation of lithospheric mantle melts in the late orogenic stage.These rocks exhibit dominantly NNE-SSW structural trend comparable those of othe Pan Africangranitoids in Nigeria. Additional trace element geochemistry, geochronology and isotopicstudies are required to ascertain the origin, age and mineral potentials of the distinct rock suitesfound in this study area.